2022
DOI: 10.3390/su14063235
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Drive Actual Purchasing of Groceries through E-Commerce Platforms during COVID-19 in Indonesia

Abstract: (1) Background: This is one of the few studies to look into online grocery shopping behavior in Indonesia, as an emerging sector of the economy. The technology acceptance model is extended in this study to include price, health risk, and a reference group to better understand the factors and the extent to which they influence online grocery shopping. (2) Methods: In order to achieve the goal of the research and test the research model, a literature-based questionnaire was developed and distributed to 300 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 97 publications
1
38
0
Order By: Relevance
“…In Indonesia, it was discovered that ease of use, usefulness, attitude, and reference group all had a statistically significant relationship with the intention and actual use of online grocery shopping platforms. However, perceived health risks were not found to be significantly correlated with respondents’ purchasing intent [ 77 ]. In Slovenia, behavioral intentions toward online shopping were analyzed under the COVID-19 pandemic and social isolation circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, it was discovered that ease of use, usefulness, attitude, and reference group all had a statistically significant relationship with the intention and actual use of online grocery shopping platforms. However, perceived health risks were not found to be significantly correlated with respondents’ purchasing intent [ 77 ]. In Slovenia, behavioral intentions toward online shopping were analyzed under the COVID-19 pandemic and social isolation circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that factors that influence the attitude and behavior of online shoppers during regular, non-emergency periods differ from those that influence their attitudes and behaviors during times of emergency. (Warganegara & Babolian Hendijani, 2022) investigated internet grocery shopping behavior. This study extends the technological acceptance model to incorporate pricing, health risk, and a reference group in order to better understand the components and their effect on online grocery shopping.…”
Section: Factors Influencing Attitudes Towards Online Shoppingmentioning
confidence: 99%
“…The severity of COVID-19 forced governments around the world to implement strict measures such as social distancing and voluntary self-isolation which led to the full or partial looked down (restricted movement of persons, goods, and services) of cities and countries [60,61]. These restrictive measures (lockdown) resulted in massive disruptions in both global and domestic supply chain systems [62,63], One of the industries that were hugely affected as a result of COVID-19 is the e-commerce (crossborder e-commerce, social commerce) environment since the restricted movement amidst social distancing measures has contributed significantly to the current changes in consumer behavior and attitudes [64,65]. Many consumers had to move their consumption (selling or purchasing of products and services) online to accommodate their daily supplies [66], Even companies that have undertaken some form of business digitalization or e-commerce were not spared from the losses occasioned by the COVID-19 Crisis regardless of their organizational size [67],…”
Section: A Covid-19 Pandemic and Consumer Behaviormentioning
confidence: 99%
“…The drastic change in consumer behavior in the era of COVID-19 caused scholars to study the dynamism of consumers in the online environment (e-commerce/social commerce). The comprehension of the factors driving consumer purchasing patterns in the periods and post-COVID-19 is important for individual and business success [64], Diverse studies have since emerged to provide useful characteristics of consumer behavior changes during and after the COVID-19 pandemic. For instance, drivers of consumer behavior during COVID-19 in Malaysia showed that perceived severity and self-isolation have a direct impact on shopping consumer behavior [68].…”
Section: A Covid-19 Pandemic and Consumer Behaviormentioning
confidence: 99%